Attitude and perception towards obesity in adolescents - Catalán Gómez, Carlos Alberto (Horizonte Sanitario, 2020)
Objective: Identify the attitude and perception toward obesity in adolescents. Material and methods: Descriptive-discursive study of integrative review. Prepared in the guide The Preferred Reporting Items for Systematic Review and Meta-Analysis Protocols (PRISMA-P), in Spanish and English, during 2010 - 2019. Databases from SciELO, Redalyc, ScienceDirect, Google Scholar, Ebsco, and Conricyt were used. For the search, DeCS descriptors were used, namely, Attitude, Perception, Adolescent, Obesity, and Nursing. From 102 identified articles, 10 were selected for analysis. Results: Adolescents have a negative attitude and perception toward obesity, because they feel excluded from society; this is identified as a serious problem because it mainly affects their psychological-social factor, since the image that others perceive of them affects their emotional state. Conclusion: It is important to work on the psychological factors in adolescents because most of them present a negative perception and an attitude of rejection. Influencing them will prevent the increase in bulling rates or, failing this, suicides, main consequences of obesity. Key Words: Attitude; Perception; Adolescent; Obesity; Nursing.